Pengaruh Interaksi Sosial di Lingkungan terhadap Pembentukan Identitas Diri Pada Remaja - Apul Perdolok Sinambela; Edy Soesanto; Dimas Hartanto (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
Adolescent identity is formed through complex interactions between various factors, in which school plays a crucial role. Schools not only serve as places of academic learning, but also as social arenas where adolescents develop interpersonal skills, values, and behavior. Factors such as relationships with peers, support from teachers, participation in extracurricular activities, and curriculum implementation all contribute to the identity formation process. This article highlights how a positive and supportive school environment can help teenagers discover their identity, build self-confidence, and develop their potential optimally. By understanding this role, it is hoped that a holistic and inclusive educational ecosystem can be created, which supports the development of adolescents towards a healthy and constructive direction. Context has been identified as an important factor in adolescent identity formation. Education plays a very important role in shaping an individual's ethics, responsibility and intelligence. An effective educational process is expected to develop students' attitudes, knowledge and skills so that they can adapt optimally to their social environment. In this context, social interactions in the school environment, especially with peers, teachers and school staff, greatly influence the formation of adolescents' self-identity. This identity formation involves a dynamic interaction between internal and external factors, where the school environment plays a significant role in shaping teenagers' thought patterns, values, attitudes and behavior. Peers serve as social references that influence adolescents' self-confidence and self-esteem, while relationships with teachers provide emotional guidance and character formation. Apart from that, social media also influences the way teenagers present themselves in the digital world. The formation of a healthy self-identity in adolescents is very dependent on an inclusive, supportive environment, as well as cooperation between schools and parents. Therefore, it is important to understand the role of social interactions in the school environment as a factor that supports the development of a positive identity in adolescents and prepares them to face life challenges in the future.